Radiation dose and fraction in immunotherapy: one-size regimen does not fit all settings, so how does one choose?. Issue 4 (7th April 2021) - Demaria, Sandra; Guha, Chandan; Schoenfeld, Jonathan; Morris, Zachary; Monjazeb, Arta; Sikora, Andrew; Crittenden, Marka; Shiao, Stephen; Khleif, Samir; Gupta, Seema; Formenti, Silvia Chiara; Vikram, Bhadrasain; et al.
Abstract : Recent evidence indicates that ionizing radiation can enhance immune responses to tumors. Advances in radiation delivery techniques allow hypofractionated delivery of conformal radiotherapy. Hypofractionation or other modifications of standard fractionation may improve radiation's ability to promote immune responses to tumors. Other novel delivery options may also affect immune responses, including T-cell activation and tumor-antigen presentation changes. However, there is limited understanding of the immunological impact of hypofractionated and unique multifractionated radiotherapy regimens, as these observations are relatively recent. Hence, these differences in radiotherapy fractionation result in distinct immune-modulatory effects. Radiation oncologists and immunologists convened a virtual consensus discussion to identify current deficiencies, challenges, pitfalls and critical gaps when combining radiotherapy with immunotherapy and making recommendations to the field and advise National Cancer Institute on new directions and initiatives that will help further development of these two fields. This commentary aims to raise the awareness of this complexity so that the need to study radiation dose, fractionation, type and volume is understood and valued by the immuno-oncology research community. Divergence of approaches and findings between preclinical studies and clinical trials highlights the need for evaluating the design of future clinical studies with particular emphasis on radiation dose and fractionation, immune biomarkers and selecting appropriate end points for combination radiation/immune modulator trials, recognizing that direct effect on the tumor and potential abscopal effect may well be different. Similarly, preclinical studies should be designed as much as possible to model the intended clinical setting. This article describes a conceptual framework for testing different radiation therapy regimens as separate models of how radiation itself functions as an immunomodulatory 'drug' to provide alternatives to the widely adopted 'one-size-fits-all' strategy of frequently used 8 Gy×3 regimens immunomodulation.